2013
DOI: 10.1016/j.cub.2013.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Flashes Orchestrate the Wound Inflammatory Response through DUOX Activation and Hydrogen Peroxide Release

Abstract: SummaryA crucial early wound response is the recruitment of inflammatory cells drawn by danger cues released by the damaged tissue. Hydrogen peroxide (H2O2) has recently been identified as the earliest wound attractant in Drosophila embryos and zebrafish larvae [1, 2]. The H2O2 signal is generated by activation of an NADPH oxidase, DUOX, and as a consequence, the first inflammatory cells are recruited to the wound within minutes. To date, nothing is known about how wounding activates DUOX. Here, we show that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
360
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(387 citation statements)
references
References 32 publications
20
360
1
1
Order By: Relevance
“…Another candidate is Ca 2+ signaling. Wounding induces fast Ca 2+ influx and Ca 2+ flashes in X. laevis oocytes and Drosophila embryo, respectively (Luxardi et al, 2014;Razzell et al, 2013). Importantly, those flashes activate a NADPH oxidase (Duox).…”
Section: Towards a Comprehensive Model Of Redox And Bioelectric Integmentioning
confidence: 99%
“…Another candidate is Ca 2+ signaling. Wounding induces fast Ca 2+ influx and Ca 2+ flashes in X. laevis oocytes and Drosophila embryo, respectively (Luxardi et al, 2014;Razzell et al, 2013). Importantly, those flashes activate a NADPH oxidase (Duox).…”
Section: Towards a Comprehensive Model Of Redox And Bioelectric Integmentioning
confidence: 99%
“…Conversely, PI3K-mediated migration is crucial for haemocytes to sense a chemotactic gradient from a wound, but not for developmental migration 46,67 . Finally, hydrogen peroxide (H 2 O 2 ) has been identified as the earliest wound attractant in Drosophila embryos and zebrafish larvae 68 . We have shown that Drosophila haemocytes are recruited towards the basal regions where cell competition is taking place to remove apoptotic cells 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Inversely, only a few studies have investigated the redox status and redox regulation of macrophage biology during tissue injury/ repair. In wound-healing models in zebrafish and Drosophila embryo, leukocyte recruitment depends on an H 2 O 2 signal gradient generated by DUOX activation (237,271).…”
Section: A Myeloid Cellsmentioning
confidence: 99%